2017
DOI: 10.15208/beh.2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Microeconomic impact of remittances on household welfare: Evidences from Bangladesh

Abstract: This paper investigates the effect of both international and domestic remittances and migration on household welfare in Bangladesh. We employ a number of variables such as different types of poverty measures, household consumption expenditure, expenditures on health and education etc to define household welfare. We use the Household Income and Expenditure survey 2010 to estimate the impact of remittance on household welfare. To address the issue of self-selection, we have used Propensity Score Matching (PSM) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 13 publications
8
35
0
2
Order By: Relevance
“…A good number of researchers studied remittances in Bangladesh (Kumar et al, 2018;Ahmed et al, 2018;Hasan and Shakur, 2017;Wadood and Hossain, 2016;Regmi and Paudel, 2016;Haider et al, 2016;Bayes et al, 2015;Hatemi-J and Uddin, 2014;Chowdhury, 2014;Masuduzzaman, 2014;Al-Mukit et al, 2013;Khan and Islam, 2013;Raihan et al, 2009). However, most of these studies are either descriptive or not focusing on the link between remittances and poverty.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A good number of researchers studied remittances in Bangladesh (Kumar et al, 2018;Ahmed et al, 2018;Hasan and Shakur, 2017;Wadood and Hossain, 2016;Regmi and Paudel, 2016;Haider et al, 2016;Bayes et al, 2015;Hatemi-J and Uddin, 2014;Chowdhury, 2014;Masuduzzaman, 2014;Al-Mukit et al, 2013;Khan and Islam, 2013;Raihan et al, 2009). However, most of these studies are either descriptive or not focusing on the link between remittances and poverty.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Khan and Islam (2013) showed that a one per cent increase in remittance inflows increases inflation rate by 2.48 per cent in the long run but no effects in the short run. Besides these impacts, remittances have significant impacts on household welfare in Bangladesh as well (Ahmed et al, 2018) and Wadood and Hossain, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…International remittances literature is crowded with studies contextualizing Bangladesh like [6,15,[37][38][39][40][41] and its relationship has been explored with numerous economic and household factors using macro-level country data. But unfortunately, its direct linkage with educational and healthcare expenditure of Bangladesh using micro-level data did not catch attention yet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rate of utilization remittance for investment purposes is too low that is 1.52 percent. Wadood and Hossain found remittance has a positive impact on consumption expenditure and no impact on education and health [31]. On the other hand, Ahmed et al found that remittances has positive and significant changes on housing condition, sources of drinking water and sanitation facilities, household accessories, education and health status of household members, household economic situation and household expenditure [32].…”
Section: Source: World Development Indicatormentioning
confidence: 99%